Repurposing the Veterinary Antibiotic Apramycin for Antibacterial and Antibiofilm Activity Against Pseudomonas aeruginosa From Cystic Fibrosis Patients - Di Bonaventura, Giovanni; Lupetti, Veronica; Verginelli, Fabio; Giancristofaro, Sara; Barbieri, Rosemary; Gherardi, Giovanni; Pompilio, Arianna (Frontiers in Microbiology, 2022)
Objectives. To evaluate the in vitro antibacterial, antibiofilm, and antivirulence activities of apramycin, comparatively to tobramycin, against a set of P. aeruginosa from chronically infected cystic fibrosis (CF) patients. Methods. The activity of antibiotics against planktonic cells has been assessed by performing MIC, MBC, and time-kill assays. The activity against mature biofilms has been evaluated, in a microtiter plate, both in terms of dispersion (crystal violet assay) and residual viability (viable cell count). The effect of drug exposure on selected P. aeruginosa virulence genes expression has been assessed by real-time Reverse Transcription quantitative PCR (RT-qPCR). Results. Apramycin MIC90 and MBC90 values have been found at least 4-fold lower than those for tobramycin. A comparable trend has been observed for mucoid strains. Only 4 out of 24 strains (16.6%) have shown an apramycin MIC higher than the epidemiological cut-off value of 64 mg/L, whereas a higher resistance rate has been observed for tobramycin (62.5%; p<0.01 vs. apramycin). In time-kill analyses, both aminoglycosides have been found bactericidal, although apramycin has shown more rapid effect and has not allowed for regrowth. Apramycin generally has stimulated biofilm biomass formation, whereas tobramycin has shown opposite trends depending on the strain tested. Both drugs have caused a highly significant, dose-dependent reduction of biofilm viability, regardless of strain and concentration tested. The exposure to apramycin and tobramycin have caused increased expression of mexA and mexC (multidrug efflux pumps), whereas tobramycin specifically has increased the expression of aprA (alkaline protease) and toxA (exotoxin A). Neither apramycin nor tobramycin have shown cytotoxic potential towards IB3-1 bronchial epithelial CF cells. Conclusions. Our results warrant future pharmacokinetic and pharmacodynamic studies for supporting the rationale to repurpose apramycin, a veterinary aminoglycoside, for CF lung infections.